ONLINE MEDIA AND WOMEN'S EMPOWERMENT: ANALYZING THE IMPACT OF VIRTUAL COMMUNITIES IN INDONESIA - Briandana, Rizki; Sofian, Muhammad Raqib Mohd (ASPIRATION Journal, 2024)
This study aims to analyze the empowerment carried out by virtual communities in Indonesia, focusing on the Sahabat Ibu Pintar community. This study explores the role of members and the level of interaction in the community as part of women's empowerment efforts. The method used in this study is netnography, with data collection techniques through interviews and observations. The results of the study indicate that economic empowerment is the main driver of activity in this virtual community. Typologically, the Sahabat Ibu Pintar community is a community formed through organizational support to run empowerment programs. In order to increase economic empowerment, this community provides access to work for its members, as well as holding online and offline training. In addition, the empowerment of this community is highly dependent on the participation and interaction of its members. Based on the purpose of communication, interactivity in this community is formed through various communication patterns, both between users and the system, between users, and between users and documents. The interactions that occur in this community contribute to expanding networks and opening up opportunities for its members to improve economic welfare.